2022
DOI: 10.1109/access.2022.3208171
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on Security Risk of LoRaWAN: Compatibility Scenarios

Abstract: The LoRaWAN standard comes from a Low Power Wide Area Network (LPWAN) technology suitable for developing Internet of Things (IoT) systems that are poised to disrupt the semiconductor industry. Even as a widespread technology used for diverse applications, security issues of long range (LoRa) networks and devices still remain a major challenge. Although the LoRa-Alliance enhanced the security and the network architecture of LoRaWAN from version 1.0 to version 1.1, the last version still faces some drawbacks suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…2) Security: Security is one of the major concerns for IoT applications. One challenge is ensuring secure authentication and authorization of the devices joining the network [84]. Another concern is the confidentiality of data during transmission.…”
Section: B Mac Layermentioning
confidence: 99%
“…2) Security: Security is one of the major concerns for IoT applications. One challenge is ensuring secure authentication and authorization of the devices joining the network [84]. Another concern is the confidentiality of data during transmission.…”
Section: B Mac Layermentioning
confidence: 99%
“…The LoRaWAN MAC protocol specifies the regulations for LoRa and defines the standards for LoRa networking. However, despite the lightweight feature, the LoraWAN protocol still faces significant threats from malicious parties [1][2][3]. Han and Wang [4] indicated that the flaws of LoRaWAN lie in the key management and data confidentiality.…”
Section: Introductionmentioning
confidence: 99%
“…In this article, we discuss in detail the LoRaWAN server and in detail discuss device management, data forwarding, security [9,10,11,12,14,15], network monitoring, and details on the Advanced Encryption Standard (AES) of the LoRaWAN server. Device management is the process of The server keeping track of all devices on the network, including their unique identifiers, current state, and data usage.…”
Section: Introductionmentioning
confidence: 99%